Engineering electronic structure of topological insulator Bi2Te3 thin films by highly uniform ripple arrays. (2nd August 2021) - Shao, Zhibin; Li, Shaojian; Bian, Qi; Cao, Yan; Sun, Haigen; Liu, Lijun; Gao, Jianzhi; Chen, Xiaorui; Li, Qing; Pan, Minghu
Abstract: 'Wrinkle engineering', as an effective approach to modify the properties of materials without introducing additional chemical doping, has been widely used in a variety of two-dimensional materials, including graphene, phosphorene and transitional metal dichalcogenides, etc. One-dimensional wrinkle or ripple arrays, which breaks the crystalline symmetry of materials, may reformate the nontrivial band structure and greatly affect the electronic properties of topological materials. Until now, such method has been rarely applied experimentally in tuning topological materials. Here, we fabricate highly uniform ripple arrays directly in few-quintuple-layers (QL) Bi2 Te3 thin films on SrTiO3 substrate realized by in-situ strained epitaxial growth, investigated by detailed low temperature scanning tunneling microscope/spectroscopy. Well-defined one-dimensional (1D) ripple structures induced by the interfacial strain from the lattice mismatch between the Bi2 Te3 films and the substrate has been observed. As the thickness of Bi2 Te3 thin films increases, the release of the strain leads to the reduction of the averaged corrugation height and the periodicity of ripple array. The dI/dV spectra and spatially resolved spectroscopic survey acquired on the epitaxial layers with different thicknesses, reveal that both the energy gap and the Fermi velocity of the Dirac surface states are greatly enhanced on thinner films. Dirac fermion velocity vF is estimated about 7.8 × 10 5 m s −1 for 3 QL, which is greatly enhanced by compared with the bulk values (4.8 × 10 5 m s −1 ). An asymmetric dispersion behavior along different Γ ˉ − M ˉ directions is observed, highly related with the modulation of 1D corrugated ripples on the electronic structure. Moreover, an unconventional Bi (S4) termination mainly observed on thinner films shows a stress-related behavior, agreed with previous theoretical calculations. Our work proposes a promising route to fabricate a highly uniform ripple structure on nontrivial topological materials, which can effectively tune the electronic structure. Specially, it may have an immediate application for realizing a high-performance topological-based device with higher operating temperature and speed.